2021
DOI: 10.1093/advances/nmab093
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Does Glycemic Index Matter for Weight Loss and Obesity Prevention? Examination of the Evidence on “Fast” Compared with “Slow” Carbs

Abstract: High-glycemic index (high-GI) foods (so-called fast carbs) have been hypothesized to promote fat storage and increase risk of obesity. To clarify whether dietary GI impacts body weight, we searched PubMed and the Cochrane Database of Systematic Reviews for observational studies reporting associations between BMI and dietary GI, and for meta-analyses of randomized controlled trials (RCTs) comparing low-GI and high-GI diets for weight loss. Data on 43 cohorts from 34 publications, totaling 1,940,968 adults, reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Indeed, in previous studies, fiber intake was associated with obesity, WHR, WC, body weight, and BMI ( 54 , 56 , 63 65 ). Also, an association was seen between GI with body weight and obesity ( 66 ). In previous studies, an inverse association was seen between whole grains with central obesity and WC ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in previous studies, fiber intake was associated with obesity, WHR, WC, body weight, and BMI ( 54 , 56 , 63 65 ). Also, an association was seen between GI with body weight and obesity ( 66 ). In previous studies, an inverse association was seen between whole grains with central obesity and WC ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the typical prospective design comparing baseline diet with future weight change will not detect prior changes that have reached steady state by the time of the dietary assessment. In this situation, bias toward null associations may ensue; thus, the lack of consistent association involving GI and GL in cohort studies is difficult to interpret [123]. To better simulate an interventional study, the relationship of change in diet to change in weight over time can be examined.…”
Section: Epidemiologymentioning
confidence: 99%
“…37 None of the cohort studies presented in Figure 2 adjusted for GI or GL in their statistical models, and thus it is possible that this could have influenced the results. However, application of GI values of foods from diet records and food frequency questionnaires used in all of the cohort studies is problematic, 39 and this may be especially true for white rice, with reported GI values ranging from 17 to 94. 40 Moreover, high consumption of white rice among Asian populations may not fully explain the higher T2D risk because high intake of white rice was not consistently associated with increased T2D risk across all Asian cohorts.…”
Section: 00mentioning
confidence: 99%